2015
DOI: 10.1186/s13075-015-0668-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two different folic acid doses with methotrexate – a randomized controlled trial (FOLVARI Study)

Abstract: IntroductionThere is reasonable evidence that folic acid 5–10 mg per week leads to reduction in methotrexate (MTX) toxicity in rheumatoid arthritis (RA). However, this is based on studies conducted with lower MTX dosage than used currently. It is unclear whether higher doses of folic acid may be better in reducing toxicity.MethodsThis was a double-blind randomized controlled trial of 24 weeks duration. To be eligible, patients should have rheumatoid arthritis (1987 American College of Rheumatology criteria), b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 33 publications
1
21
0
1
Order By: Relevance
“…Dhir V et al reported that additional folic acid use at doses more than 10 mg/week for the treatment of adverse effects caused by high dose methotrexate had little advantage over the therapy with usual dose of folic acid [6]. These observations are consistent with our present findings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Dhir V et al reported that additional folic acid use at doses more than 10 mg/week for the treatment of adverse effects caused by high dose methotrexate had little advantage over the therapy with usual dose of folic acid [6]. These observations are consistent with our present findings.…”
Section: Discussionsupporting
confidence: 93%
“…Major conclusion Folic acid dose was dependent on the hospitals, while efficacies and hepatotoxicity of methotrexate was not basically different between patients taking less and more than 5 mg/week of folic acid. of folic acid 24-48 h after the methotrexate administration [6]. However, the dose of folic acid may be independently determined among the hospitals or physicians, while folic acid at doses more than 5 mg/week may influence the efficacies of methotrexate.…”
Section: Introductionmentioning
confidence: 99%
“…5mTHF) [59]. However, it is interesting to note that associations between higher baseline erythrocyte folate levels and lower disease activity scores after 3 months of MTX therapy was observed in one of the studies [57] and reduced serum folates levels at baseline were associated with 'undesirable symptoms' related to MTX therapy in the other [58]. These findings require further study to determine the potential role of monitoring circulating folate levels in the treatment of JIA, in particular, studies are needed to see if variation in folate levels can account for the observed variations in drug efficacy and toxicity.…”
Section: Folates In Mtx Therapymentioning
confidence: 93%
“…Interestingly, folic acid supplementation was documented in 47% of patients receiving MTX, but was not found to be associated with any difference in circulating 5mTHF levels. In contrast to these findings, two recent studies in RA patients that utilized competitive folate binding protein immunoassays to measure serum and erythrocyte folate found that initiation of MTX therapy along with folic acid supplementation at levels of 10-30 mg/week resulted in no significant reduction in serum or erythrocyte folate levels [57,58]. The origin of this discrepancy may reflect differences in the level of folate supplementation in the studies, innate differences in systemic folate regulation in pediatric versus adult patients, or more than likely, differences in the analytical methodologies marked by the inability of competitive folate binding protein assays to distinguish between individual folate species with a higher affinity of these proteins for the inactive supplemental form of folate (i.e.…”
Section: Folates In Mtx Therapymentioning
confidence: 96%
“…To avoid side effects, split doses of MTX administration and folate supplementation are gradually being used in ophthalmic clinic. Prescription of 5 to 10 mg of folate supplementation has a significant role in MTX safety [ 128 ], but the higher dosage is less applied, even with higher dose of MTX [ 129 ]. Prophylactic folate supplementation is not necessary in most patients [ 130 ].…”
Section: Discussionmentioning
confidence: 99%